Evaluating Nutritional Selection and Outcomes in Neonatal Abstinence Syndrome: A Retrospective Review - Gallegos, Juan A.; Serke, Laura; Feygin, Yana; Jawad, Kahir; Robinson, Tonya; Telang, Sucheta (American Journal of Perinatology, 2024)
The rising incidence of neonatal abstinence syndrome (NAS) has amplified the importance of nonpharmacological interventions in its management, which include the selection of feedings. With the goal of obtaining an accurate assessment of the effects of current feeding practices in NAS infants in our neonatal intensive care unit, we conducted a retrospective review of NAS infants at our hospital over a 3-year period to determine their nutritional selections and evaluate their length of stay (LOS), length of treatment (LOT), and growth outcomes.Retrospective chart review of term infants (≥37 weeks of gestation) with NAS. Maternal and infant demographics and characteristics were recorded. Infants were grouped based on majority (>50% of total feeding) nutritional selections and LOS, LOT, and growth parameters were evaluated. Linear regression was used to compare group outcomes. Significance was set at a p-value <0.05.A total of 70 infants were included and grouped based on majority feeds into maternal breast milk (MBM), standard term formula (STF), low lactose formula (LLF), and extensively hydrolyzed formula (EHF) groups. Feeding selections were provider-dependent and infants were placed on MBM or STF as an initial selection. In all infants included in our review, LLF was selected as the first choice following MBM or STF for increased gastrointestinal (GI) disturbance-related Finnegan Neonatal Abstinence Scoring scores and changed to EHF if LLF failed to improve the GI-related symptoms. The STF-fed infants had the shortest LOS, and none of these infants required pharmacological treatment. The LOT and LOS were similar in the MBM- and LLF-fed groups. Infants who were EHF fed had the longest LOT and LOS. All feeding groups demonstrated appropriate growth.Nutritional selections in our NAS infants were modified for the severity of their withdrawal symptoms. All nutritional modifications driven by severity of withdrawal symptoms supported favorable growth outcomes in the infants.
Keywords: neonatal abstinence syndrome; opioids; drug withdrawal; nutrition; formula; maternal breast milk; hydrolyzed formula